The effect of salary, bonuses, and work facilities on employee performance - Andini Nur Faizah; Dina Fahma Sari; Agus Andi Subroto; Yusma Eka Pangestu; Audry Shatara (Indonesia Auditing Research Journal, 2025)
In the current economic climate, salary levels significantly influence employee welfare. According to the 2024 data from the Central Statistics Agency (BPS) on regional minimum wages, Pasuruan is among the regions with relatively high minimum wages in East Java. However, this does not necessarily guarantee the welfare of Non-Civil Servant (Non-ASN) employees, who continue to face disparities due to the lack of clear regulations regarding basic rights such as salary, bonuses, and work facilities. This study aims to analyze the influence of salary, bonuses, and work facilities on the performance of Non-ASN employees at the Department of Transportation of Pasuruan City. A descriptive quantitative method was used, with a saturated sampling technique involving 78 Non-ASN employees as respondents. Data were collected through questionnaires and analyzed using IBM SPSS Statistics 26. The results show that salary does not have a significant effect on employee performance, as it is considered a fixed component. In contrast, bonuses and work facilities have a significant effect, as both serve as supporting factors that enhance productivity. Simultaneously, all three variables significantly influence employee performance, indicating a strong interrelationship in improving overall work outcomes.